Paletero man! = ¡Qué paletero tan cool! - Diaz, Lucky (HarperEspañol, an imprint of HarperCollins Publishers, 2022)
"Follow along with our narrator as he passes through his busy neighborhood in search of the Paletero Man. But when he finally catches up with him, our narrator's pockets are empty. Oh no! What happened to his dinero? It will take the help of the community to get the tasty treat now"--Provided by publisher.